The Assessment and Allocation of Public Private Partnership Risks in the UAE - Shaban, Mazhd (2022)
A Master of Science thesis in Construction Management by Mazhd Shaban entitled, “The Assessment and Allocation of Public Private Partnership Risks in the UAE”, submitted in April 2022. Thesis advisor is Dr. Irtishad Ahmad and thesis co-advisor is Dr. Sameh El-Sayegh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).